An implementation of a CODASYL based data management system under the UNIX operating system. - Howard, John Edward (Monterey, California: Naval Postgraduate School, 1976)
This thesis reports the implementation of a Data Base Management System (DBMS) based on the CODASYL design. The DBMS was implemented on a DEC PDP 11/50 computer utilizing the UNIX operating system. Background material includes a discussion of data base history and techniques, design of UNIX AND THE C programming language. The research performed was the adaptation of the CODASYL DBMS design to the UNIX environment and the design of a C language Data Description Language (DDL) and Data Manipulation Language (DML) to interface the DBMS to user programs. Conclusions and recommendations for improvements are also included. Approved for public release; distribution is unlimited. Captain, United States Marine Corps http://archive.org/details/animplementation1094517807